Development of real-time PCR assay for the early diagnosis, treatment response prediction and monitoring of nasopharyngeal carcinoma (NPC) disease - Abusalah, Mai Abdel Haleem A. (2021)
Nasopharyngeal carcinoma (NPC) is a non-lymphomatous squamous cell carcinoma that develops in the epithelial cells layer covering the surface of the nasopharynx. NPC is considered a diagnostic challenge to clinicians due to the difficulty in nasopharynx examination, and non-specific symptoms. The Epstein–Barr virus (EBV) is well-associated with NPC. In addition, EBV LMP1 30 bp deletion was shown to play a vital role in enhanced oncogenic behaviour of EBV infected cells and results in more aggressive EBV-related tumour phenotypes. Therefore, this study intended to develop an innovative Taqman hydrolysis probe-based qPCR to detect the EBV's LMP1 30 bp deletion using whole blood samples from NPC patients. This developed assay will help the clinicians in early diagnosis, treatment response prediction, understand the extent of treatment effectiveness, and follow-up monitoring of NPC patients after treatment. In this developed i-qPCR, the mutant-specific primers, probes and multi-points degenerative blocker were designed. The Taqman hydrolysis probe-based qPCR parameters to detect the EBV's LMP1 30 bp deletion were also optimised. Internal control (IAC) was incorporated to rule out the false negative result. The demographic data of NPC patients were collected and used in the statistical analysis of this study. The assay validation was accomplished based on MIQE guidelines. The developed assay's analytical sensitivity was performed using 10-fold serial dilutions of MT gBLOCK (synthetic DNA). The analytical specificity was evaluated using 48 bacterial, fungal and virus genomic DNA and 12 extracted genomic DNA from archived biopsy tissue and fine-needle aspiration samples of NPC patients. The diagnostic evaluation of the developed assay was performed on 109 prospective specimens from NPC patients, non-NPC cancer patients and healthy individuals. The LOD of this developed assay was 173 copies/assay. The diagnostic evaluation showed 100% specificity, 83.3% sensitivity, 100% PPV and 98.7% NPV. A significant association was found between clinician treatment response prediction and Cq values of 30 bp deletion in this study (P-value= 0.033). In conclusion, this study was effective in developing an i-qPCR assay for early detection of 30 bp deletion tumour marker with high specificity and sensitivity, to help clinicians in treatment response prediction, and determine treatment effectiveness among NPC patients.